PENATAAN JARINGAN DRAINASE UNTUK REKLAMASI RAWA PADA BUDIDAYA SAGU DI KAIS - Fachrul, Rully (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
The Sago Plant in the Kais Region, South Sorong Regency, has significant potential as an alternative food source to rice. Currently, sago plant management remains traditional or non-technical, particularly in preparing water management requirements, specifically through technical drainage management for the Sago Plant. Generally, the local community indicates that efforts to improve sago plant management are constrained by drainage issues due to water conditions affected by tidal changes, which impact the root zone of the sago plants. Efforts to address these issues include the development of a Technical Drainage System throughout the sago plantation area. Therefore, this study aims to understand the application of a Technical Drainage System that will be implemented in the management of sago plants in the Kais Region, South Sorong Regency. This research involves analyzing both secondary and primary data available. The study begins with a literature review, data collection (including oceanographic data, topographic maps, and bathymetric maps), and field surveys (secondary data collection). All data will be used as input for the model and validated with satellite imagery and bathymetric maps. Based on existing river line changes and numerical model results, an analysis of river line changes and alternative drainage systems will be conducted as solutions for sago plant management